PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI SHOWROOM DICKY JAYA MOTOR KECAMATAN CIPONGKOR, KABUPATEN BANDUNG BARAT - Rijaldi, Diki; Sutira, Andri (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2024)
Customer satisfaction is a person's level of satisfaction which is measured based on the comparison between the perceived performance and the expectations they have. Factors that can affect customer satisfaction include service quality, product quality, and price. This study aims to analyze the influence of service quality on customer satisfaction at the Dicky Jaya Motor Showroom. This study uses a quantitative approach with a sample of 50 Dicky Jaya Motor Showroom customers. The data obtained was analyzed using SPSS version 26 software. The results of the analysis show that the service quality variable (X) has a significant influence on customer satisfaction (Y). This is evidenced by a t-cal value of 6.262 which is greater than the t-table of 2.010 at a significance level of 0.000 < 0.05. Based on these results, the null hypothesis (H0) was rejected, and the alternative hypothesis (Ha) was accepted, which means that the quality of service contributed significantly to customer satisfaction at the Dicky Jaya Motor Showroom. This study concludes that service quality is an important factor in determining customer satisfaction, so efforts to improve service quality need to be a priority to support business success in the automotive sector.